Subaltern of the Subalterns: - Sanjida Chowdhury (Crossings, 2017)
In India the complex social structure demands that it be divided into heterogeneous classes. This division produces class discrimination as well as caste discrimination. The latter has been institutionalized in the name of religion; and the upper castes, using religious dogma, assume hegemonial power to exploit the lower castes to suppress them economically, socially, and politically. Mulk Raj Anand has shown the pathetic condition of the outcaste/ untouchable in colonial India where the whole of India is subjugated to their colonizers, and because of the division and subdivision, the lower castes are subjugated at the hands of the upper caste Hindus. The condition of the untouchables cannot be recognized by generalizing them as subalterns; rather they demand a critical study beyond the accepted notion regarding the synonymous use of “people” and “subaltern.” This paper argues the possibility of reviewing the untouchables in a double subalternized position in the context of Mulk Raj Anand’s Untouchable.